Pathogens manipulate host autophagy through injected effector proteins. Issue 12 (1st December 2020) - Lal, Neeraj K.; Thanasuwat, Burinrutt; Chan, Barry; Dinesh-Kumar, Savithramma P.
ABSTRACT: Macroautophagy/autophagy plays a dual role in many physiological processes of multicellular eukaryotes. In plants, autophagy can be used by both host and pathogen for a beneficiary infection outcome. Plants employ a two-tier innate immune system to defend against invading pathogens. Cell surface localized pattern recognition receptors recognize conserved pathogen-associated molecular patterns (PAMPs) and launch pattern-triggered immunity (PTI) to provide broad-spectrum resistance. Pathogens inject a battery of effector proteins into their hosts to counter PTI and compromise the primary immune response. Hosts induce a second layer of defense called effector-triggered immunity (ETI) to counter the effects of these effectors. In addition to ETI and PTI, autophagy is emerging as a central cellular process modulated by both host and pathogens toward their respective advantage. Pathogens lacking the ability to inject effectors are compromised in virulence. However, molecular targets and biochemical characterization of most of these effector proteins remain elusive. In a recent paper we presented a systematic analysis of interaction between autophagy proteins of Arabidopsis thaliana with effectors from bacterial, fungal, oomycete and nematode pathogens. Abbreviations : ATG, a ut ophag y related; BiFC, b imolecular f luorescence c omplementation; ETI, effector-triggered immunity; PAMPs, pathogen-associated molecular patterns; PTI, pattern-triggered immunity